Aortic valve perforation in the setting of Cogan's syndrome. Issue 8 (27th June 2019) - Beltagy, Asmaa; Eshak, Nouran; Abdelnabi, Mahmoud Hassan; Almaghraby, Abdallah; Magdy, Samar; Shehata, Hoda
Abstract: Cogan's syndrome is a rare disorder characterized by the coexistence of ocular and audio‐vestibular manifestations. Systemic manifestations are quite unusual with pan‐vasculitis and cardiac involvement reported in the form of aortitis with aortic aneurysm, dissection, or extremely rare aortic valve perforation. Hereby, we report a case of a 56‐year‐old woman presented with ocular, audio‐vestibular, and systemic manifestations with medium‐sized vasculitis in the form of multiple splenic artery aneurysms, superior mesenteric artery thrombosis, and cardiovascular involvement in the form of aortic regurgitation due to noncoronary cusp perforation. To the best of our knowledge, this is the second case to report aortic perforation in the setting of Cogan's syndrome.